Changes in Polar Metabolites during Seed Germination and Early Seedling Development of Pea, Cucumber, and Wheat - Joanna Szablińska-Piernik; Lesław Bernard Lahuta (Agriculture, 2023)
Seed-to-seedling transition plays a crucial role in plant vegetation. However, changes in the metabolome of crop seedlings during seed germination and early seedling development are mostly unknown and require a deeper explanation. The present study attempted to compare qualitative and quantitative changes in polar metabolites during the seed germination and early development of seedlings of three different and important crop types: pea, cucumber, and wheat. The application of gas chromatography coupled with a flame ionization detector, as well as gas chromatography coupled with mass spectrometry, identified 51 polar metabolites. During seed imbibition/germination, the rapid degradation of raffinose family oligosaccharides (RFOs) preceded a dramatic increase in the concentrations of intermediates of glycolysis and the TCA cycle in embryonic axes (of pea and cucumber) or embryos (of wheat), confirming the important role of RFOs in the resumption of respiration and seed-to-seedling transition. After germination, the metabolic profiles of the growing roots, epicotyl/hypocotyl/coleoptile, and cotyledons/endosperm changed according to fluctuations in the concentrations of soluble carbohydrates, amino acids, and organic acids along the timeline of seedling growth. Moreover, the early increase in species-specific metabolites justified their role in seedling development owing to their participation in nitrogen metabolism (homoserine in pea), carbon translocation (galactinol, raffinose, and stachyose), and transitory carbon accumulation (1-kestose in wheat). The obtained metabolic profiles may constitute an important basis for further research on seedling reactions to stress conditions, including identification of metabolic markers of stress resistance.